PEMODELAN KECEPATAN ALIRAN DARAH PADA DOMAIN MENYERUPAI PEMBULUH DARAH DENGAN FEATOOL MULTIPHYSICS - Andika Thoibah; Defrianto Defrianto; Saktioto Saktioto (Komunikasi Fisika Indonesia, 2023)
Currently, computer-based simulation methods are widely used in blood flow analysis. The application of this method has been widely used in modeling blood vessels. This article presents an example of a simple blood vessel modeling to determine the velocity of blood flow to the viscosity of blood in the blood vessels. The mathematical model of human blood flow through vascular ramifications was studied using finite element analysis (FEA), which is applied to the stable two-dimensional flow of viscous fluids through various shapes. Flow through a two-dimensional model of aortic vessels, capillaries, and veins is simulated. The velocity distribution through the blood vessels is calculated. The validity of the calculation method is determined by comparing the numerical results with other results. The implementation of the Navier-Stokes equation in a vascular model using the finite element method shows that the velocity of blood flow depends on the viscosity. The higher the viscosity of the blood, the slower the rate of blood flow in the veins.